1997
DOI: 10.1007/bf03161977
|View full text |Cite
|
Sign up to set email alerts
|

Muon studies of organic ferromagnets and conductors

Abstract: Abstraet. Muon spin rotation (~tSR) experiments can be especially helpful in the study of various organic molecular materials. The technique has been used to study the magnetization in nitronyl nitroxide organic ferromagnets, the spin-density-wave ground state in various charge transfer salts, the dynamics of carriers in organic eonductors and the vortex structures in organic superconductors. I outline the motivation for studying these new materials and review and discuss the results of recent work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Most strikingly, of course, many of these ET 2 X systems show transitions to a superconducting phase at temperatures of up to around 13 K. Muon studies on these systems have served to give information on carrier dynamics and on vortex structures in the superconducting state. 6 Fourier transformation of the precession/relaxation function yields the three-dimensional structure of the internal field distribution. Field cooling studies on Ä-(BEDT-TTF) 2 Cu(SCN) 2 showed the presence of a linear vortex lattice at low fields and temperatures, with a transition to a quasi-2D lattice at higher fields (B > ¾7 mT) and breakup of the vortex line at higher temperatures (T b > ¾5 K).…”
Section: Introductionmentioning
confidence: 99%
“…Most strikingly, of course, many of these ET 2 X systems show transitions to a superconducting phase at temperatures of up to around 13 K. Muon studies on these systems have served to give information on carrier dynamics and on vortex structures in the superconducting state. 6 Fourier transformation of the precession/relaxation function yields the three-dimensional structure of the internal field distribution. Field cooling studies on Ä-(BEDT-TTF) 2 Cu(SCN) 2 showed the presence of a linear vortex lattice at low fields and temperatures, with a transition to a quasi-2D lattice at higher fields (B > ¾7 mT) and breakup of the vortex line at higher temperatures (T b > ¾5 K).…”
Section: Introductionmentioning
confidence: 99%
“…Usually this may also be neglected in superconductors, since the superconducting widths of the spectra (given by the value of the penetration depth) are approximately an order of magnitude larger than those arising from the nuclear moments. In superconductors with very long penetration depths, however, such as the organic charge transfer ET (ET -BEDT-TTF = bis(ethylenedithio)-tetrathiafulvalene) salts [15][16][17], the nuclear broadening is of the same order as the superconducting contribution to the linewidth. In that case the determination of the penetration depth from Eq.…”
Section: Field Distributions Of Vortex Latticesmentioning
confidence: 99%
“…The line below the transition has a weighting to fields higher than the average, whereas above the transition the converse is true. This is shown by a change in sign of the lineshape asymmetry parameter (17) The sharpness of the temperature dependence of a suggests the first order nature of the transition. This is shown in Fig.…”
Section: Field Distributions Of Vortex Latticesmentioning
confidence: 99%
“…µSR (for details of the technique and background information, see [6][7][8]) is a powerful technique which has been extensively applied to organic materials with unusual ground states (for a recent review, see [9]). Measurements on organic ferromagnets in zero magnetic field 0953-8984/98/4710701+13$19.50 c 1998 IOP Publishing Ltd directly probe the local magnetic field at the muon site and can be easily carried out down to a few tens of mK.…”
Section: Introductionmentioning
confidence: 99%